UPAYA PEMERINTAH JEPANG DALAM MENANGANI PEMBAJAKAN MANGA SERTA ANIME DI TIONGKOK (2020-2022) - Fadhila, Duta Maulana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research was conducted based on the rampant manga and anime piracy experienced by the Japanese as creators, which caused the Japanese government to experience enormous losses. so that the pirated site is not hit by a takedown, whether it’s by using a new web, a new domain or other sneaky ways to make the site safe from the security carried out by the Japanese. Not only that, the Japanese have also taken many preventive measures, but there are still gaps that can be passed for pirates to carry out their actions. action on the distribution of pirated manga, by making laws and regulations and punishments for the perpetrators of piracy, the Japanese have been able to reduce the number of existing piracy, but cannot prohibit it, with piracy still existing, the Japanese are still very dangerous about this version. This research uses qualitative methods, where this research uses books, e-books, journals, e-journals, websites, and also other literature studies. This study uses the perspective of Pluralism as well as role theory and the theory of protection of intellectual property rights. The results of this study are, with Japan’s losses which are estimated to reach trillions of yen in 2020-2022, Japan has succeeded in suppressing existing piracy rates, as well as making regulations and also being a pioneer in the creation of a new organization under the auspices of CODA, namely the International Anti-Piracy Organization (IAPO). Keywords: piracy, manga, anime, loss